A Path to a Countermovement? Forms of Integration in Polish Consumer Cooperatives - Bilewicz, Aleksandra (Praktyka Teoretyczna, 2018)
This paper discusses Polish consumer cooperatives in terms of the embedded economy as understood by Karl Polanyi. The author compares today‟s “new” cooperatives, or informal groups of consumers that have been emerging in Poland since 2010, with the “old” consumer cooperative movement that existed between 1906 and 1939, as represented mainly by the “Społem” consumer cooperative union. Following Polanyi‟s understanding of the relationship between human economy and social institutions, I analyse reciprocity and redistribution as forms of economic integration in past and present cooperatives. Although the “new” cooperatives refer to the prewar cooperative traditions, their structure and economic operation differ vastly from the original model. I argue that the present structure of consumer cooperatives does not provide a base for symmetry and centricity – “supporting structures” for reciprocity and redistribution – although some of the new cooperatives do offer solutions for those deficits. This paper also discusses the nature of class barriers in the contemporary and historical consumer-cooperative movement, and relates this issue to Polanyian notions of countermovement and class interest.